PERILAKU MEMILIH BURUH ROKOK DALAM PILKADA LANGSUNG DI KABUPATEN KUDUS TAHUN 2008 - Dicky Priambodo; Purwoko .; Kushandajani . (Journal of Politic and Government Studies, 2014)
The regional head and deputy regional head directly for the first time for the district Holy. The process of the election of the Holy regent and deputy regent has taken place on April 12 2008 Everyone knows, that is the Holy city of clove cigarette industry, a place where there are thousands of factories large and small cigarettes which give employment to the inhabitants. More than a hundred thousand people working in this sector. Most of them are as cigarette workers. The interesting thing is that in the This election their voices became seizure, even one candidate targeting him main, the pair Mansour As'ad and Agus Darmawan. This study aims to determine and identify the dominant factors affecting voter behavior cigarette workers in the implementation of direct elections in the Holy district. The process of data collection conducted through literature review, interviews, direct observation, then manage and analyzing the data with the results of a descriptive qualitative techniques. Based on the results of the study concluded that the first of the factors that affect voter behavior in elections Holy cigarette workers in 2008, the first row is a factor interpreter campaign or the campaign team. It is heavily influenced by the attitude of cigarette workers who tend to be passive in political activities, most of them are women, most of the time is used to work and they tend to not want to engage the conflict so that their voices of people who depend on surrounding.The second factor is the political incentives or grants or whatever. It is very closely related with a pragmatic attitude, they lack confidence in whether the elections will bring changes to the future for the better. The third factor is the identification of a candidate, they will select candidates according to behavior is good news and want to come and visit the community down. The fourth factor is issue campaign or candidate's vision and mission. Vision Mission and campaign promises of candidates that are too long will not be read, remembered and understood by the workers, campaign promises are practical and can be billed if laterelected more hit. The fifth factor is party identification, candidate of major parties such as PDI-P, Golkar, PKB and PPP has an influence as well known but solid party factor is more prominent, for they how the party would govern if care is not just incompetent. The sixth factor is the pressure group or pressure groups. Most of them are women and the lower class workers, who extremely susceptible to mobilization and pressure. At first, researchers consider the most pressure groups is the dominant union because the union chairman has a target, it turns out the workers are not afraid of dreaded union not a union but the company owner, while the owner of the company committed to neutral. Pressure groups are more dominant is the surrounding non-Sabet liberate their thinking and determine their own choice. Limited access to information and economy makes them easy mobilized.Keywords: cigarette workers voting behavior, elections Jump, Holy District 2008